Evaluation of Rice Germplasm under Salt Stress at the Seedling Stage through SSR Markers - Al-Amin, M; Islam, MM; Begum, SN; Alam, MS; Moniruzzaman, M; Patwary, MAK (International Journal of Agricultural Research, Innovation and Technology, 2013)
Twenty eight rice germplasms were used for identification of salt tolerant rice genotypes at the seedling stage at the experimental farm and Biotechnology laboratory of the Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh during February 2009 to October 2009. Phenotyping for salinity screening of the rice genotypes was done using salinized (EC level 12 dS m-1) nutrient solution in hydroponic system. Genotypes were evaluated for salinity tolerance on 1-9 scale based on seedling growth parameters following modified Standard Evaluation Scoring (SES) of IRRI. Phenotypically, on the basis of SES and % total dry matter (TDM) reduction of the genotypes viz. PBSAL-614, PBSAL-613, PBSAL-730, Horkuch, S-478/3 Pokkali and PBSAL (STL)-15 were found to be salt tolerant; on the other hand Iratom-24, S-653/32, S-612/32, S-604/32, S-633/32, Charnock (DA6), BINA Dhan-6 and S-608/32 were identified as salt susceptible. For genotyping, ten SSR markers were used for polymorphism, where 3 primers (RM127, RM443 and RM140) were selected for evaluation of salt tolerance. In respect of Primer RM127, 7 lines were found salt tolerant and 11 lines were moderately tolerant and 10 lines were susceptible. Nine tolerant, 9 moderately tolerant and 10 susceptible lines were found when the primer RM140 was used and primer RM443 identified 8 lines as tolerant, 9 lines as moderately tolerant and 11 lines as susceptible. Thus, the salt tolerant lines can be used in further evaluation for salinity tolerance and the SSR markers used in this study are proving valuable for identifying salt tolerant genes in marker assisted breeding. Int. J. Agril. Res. Innov. & Tech. 3 (1): 52-59, June, 2013 DOI: http://dx.doi.org/10.3329/ijarit.v3i1.16093